A study of anemia among adolescent females in the urban area of Nagpur - Chaudhary Sanjeev; Dhage Vasant (Wolters Kluwer Medknow Publications, 2008)
Objectives: To estimate the prevalence of anemia among adolescent females and to study the socio-demographic factors associated with anemia. Materials and Methods: A cross-sectional survey was conducted in an urban area under Urban Health Training Center, Department of Preventive and Social Medicine, Government Medical College and Hospital, Nagpur. A total of 296 adolescent females (10-19 years old) were included in this study. The study took place from October 2002 to March 2003 (6 months). Statistical analyses were done using percentage, standard error of proportion, Chi-square test, and Student′s ′t′ test. Results: The prevalence of anemia was found to be 35.1%. A significant association of anemia was found with socio-economic status and literacy status of parents. Mean height and weight of subjects with anemia was significantly less than subjects without anemia. Conclusions: A high prevalence of anemia among adolescent females was found, which was higher in the lower socio-economic strata and among those whose parents were less educated. It was seen that anemia affects the overall nutritional status of adolescent females.